The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1111/j.2044-8260.1982.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Icon thresholds in paranoid and non‐paranoid schizophrenics

Abstract: Recent work in information processing points to two processes being active when a stimulus produces a short‐term memory trace, the icon. Previous work in schizophrenia seems to have blurred this important distinction and as a result the processing of the icon has been confused with the strength of the icon. The present paper reviews current work with this distinction in mind and presents data on the icon strength of acute paranoid and non‐paranoid schizophrenics, chronic schizophrenics, and two control groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1985
1985
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…Within the Type A masking paradigm, which has been traditionally employed by schizophrenia researchers, the CSD has been regarded as a measure of icon quality, whereas backward masking functions have been thought to reflect the speed of information transfer from the icon to short-term memory.I Studies that have employed a CSD methodology have produced mixed results. Although it has been demonstrated that both college students with a 2-7-8 MMPI schizotypic profile and some process schizophrenics evidence abnormally high CSDs (Merritt & Balogh, 1984a, 1984b, this input deficit has not been uniformly exhibited among individuals within the schizophrenia spectrum (Magaro & Page, 1982). The results of the current investigation add little in the way of clarification, inasmuch as the presumably vulnerable subjects demonstrated CSD performance equivalent to that of the normal subjects.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Within the Type A masking paradigm, which has been traditionally employed by schizophrenia researchers, the CSD has been regarded as a measure of icon quality, whereas backward masking functions have been thought to reflect the speed of information transfer from the icon to short-term memory.I Studies that have employed a CSD methodology have produced mixed results. Although it has been demonstrated that both college students with a 2-7-8 MMPI schizotypic profile and some process schizophrenics evidence abnormally high CSDs (Merritt & Balogh, 1984a, 1984b, this input deficit has not been uniformly exhibited among individuals within the schizophrenia spectrum (Magaro & Page, 1982). The results of the current investigation add little in the way of clarification, inasmuch as the presumably vulnerable subjects demonstrated CSD performance equivalent to that of the normal subjects.…”
Section: Discussioncontrasting
confidence: 65%
“…Studies that have employed a CSD methodology have produced mixed results. Although it has been demonstrated that both college students with a 2–7–8 MMPI schizotypic profile and some process schizophrenics evidence abnormally high CSDs (Merritt & Balogh, 1984a, 1984b; Saccuzzo & Braff, 1981), this input deficit has not been uniformly exhibited among individuals within the schizophrenia spectrum (Magaro & Page, 1982). The results of the current investigation add little in the way of clarification, inasmuch as the presumably vulnerable subjects demonstrated CSD performance equivalent to that of the normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although a CSD deficit has not been demonstrated by all schizophrenic subgroups or schizotypic groups (Magaro & Page, 1982; Nuechterlein & Dawson, 1984), susceptibility to backward masking has been consistently demonstrated by many of these groups (Balogh & Merritt, 1985a, 1985b; Braff, 1981; Braff & Saccuzzo, 1981, 1982; Merritt & Balogh, 1984b, 1985; Miller, Saccuzzo, & Braff, 1979; Saccuzzo & Braff, 1981; Saccuzzo, Hirt, & Spencer, 1974; Saccuzzo & Miller, 1977; Saccuzzo & Schubert, 1981; Schwartz, Winstead, & Adinoff, 1983).…”
mentioning
confidence: 99%
“…The values of the critical exposure durations are somewhat higher than those in previous studies. Normal controls have demonstrated mean thresholds ranging from 10 to 15 ms [Brody et al, 1980;Magaro and Page, 1982], Depressive patients have var ied from 7 to 15 ms Saccuzzo and Braff, 1981]. Threshold values and extremely depen dent on factors such as luminance, familiarity and com plexity of the stimuli, and possibly on age.…”
Section: Discussionmentioning
confidence: 99%
“…Single letters and strings or arrays of letters have been used as stimuli. With single letters the subjects are requested to recognize the stimulus at a minimum or critical exposure duration [Warrington and James, 1967;Braff and Saccuzzo, 1981;Magaro and Page, 1982], Threshold durations of exposure for correct recognition of shorter strings of letters have been as sessed, as a measure of perceptual span [Schonfield and Wenger, 1975;Cash et al, 1972]. Further, with strings or arrays of letters, the subject can be asked to recognize and report as many of the stimuli as possible at a fixed expo sure duration ('whole report technique') [Sperling, 1963], or to report only randomly designed portions of a larger array of letters ('partial report technique') [Sperling, 1960;Averbach and Coriell, 1961].…”
Section: Introductionmentioning
confidence: 99%